Not a Routine Case, Why Expect the Routine Outcome? Quantifying the Infectious Burden of Emergency General Surgery Using the NSQIP. Issue 9 (September 2019) - Arnold, Michael R.; Kao, Angela M.; Cunningham, Kyle W.; Christmas, A. Britton; Thomas, Bradley W.; Sing, Ronald F.; Reinke, Caroline E.; Ross, Samuel W.
Emergent surgeries have different causes and physiologic patient responses than the same elective surgery, many of which are due to infectious etiologies. Therefore, we hypothesized that emergency cases have a higher risk of postoperative SSI than their elective counterparts. The ACS NSQIP database was queried from 2005 to 2016 for all cholecystectomies, ventral hernia repairs, and partial colectomies to examine common emergency and elective general surgery operations. Thirty-day outcomes were compared by emergent status. Any SSI was the primary outcome. There were 863, 164 surgeries: 416, 497 cholecystectomies, 220, 815 ventral hernia repairs, and 225, 852 partial colectomies. SSIs developed in 38, 865 (4.5%) patients. SSIs increased with emergencies (5.3% vs 3.6% for any SSI). Postoperative sepsis (5.8% vs 1.5%), septic shock (4.7% vs 0.6%), length of stay (8.1 vs 2.9 days), and mortality (3.6% vs 0.4%) were increased in emergent surgery; P < 0.001 for all. When controlling for age, gender, BMI, diabetes, smoking, wound classification, comorbidities, functional status, and procedure on multivariate analysis, emergency surgery (odds ratio 1.15, 95% confidence interval 1.11–1.19) was independently associated with the development of SSI. Patients undergoing emergency general surgery experience increased rates of SSI. Patients and their families should be appropriately counseled regarding these elevated risks when consenting for emergency surgery.